SiaA/D interconnects c-di-GMP and RsmA signaling to coordinate cellular aggregation of pseudomonas aeruginosa in response to environmental conditions - Colley, Brendan (2018)
Pseudomonas aeruginosa has emerged as an important opportunistic human pathogen that is often highly resistant to eradication strategies, mediated in part by the formation of multicellular aggregates. Cellular aggregates may occur attached to a surface (biofilm), at the air-liquid interface (pellicle), or as suspended aggregates. Compared to surface attached communities, knowledge about the regulatory processes involved in the formation of suspended cell aggregates is still limited. We have recently described the SiaA/D signal transduction module that regulates macroscopic cell aggregation during growth with, or in the presence of the surfactant SDS. Targets for SiaA/D mediated regulation include the Psl polysaccharide, the CdrAB two-partner secretion system and the CupA fimbriae. While the global regulators c-di-GMP and RsmA are known to inversely coordinate cell aggregation and regulate the expression of several adhesins, their potential impact on the expression of the cupA operon remains unknown. Here, we investigated the function of SiaA (a putative ser/thr phosphatase) and SiaD (a di-guanylate cyclase) in cupA1 expression using transcriptional reporter fusions and qRT-PCR. These studies revealed a novel interaction between the RsmA posttranscriptional regulatory system and SiaA/D mediated macroscopic aggregation. The RsmA/rsmY/Z system was found to affect macroscopic aggregate formation in the presence of surfactant by impacting the stability of the cupA1 mRNA transcript and we reveal that RsmA directly binds to the cupA1 leader sequence in vitro. We further identified that transcription of the RsmA antagonist rsmZ is controlled in a SiaA/D dependent manner during growth with SDS. Finally, we found that the siaD transcript is also under regulatory control of RsmA and that overproduction of RsmA or the deletion of siaD results in decreased cellular cyclic di-guanosine monophosphate (c-di-GMP) levels quantified by a transcriptional reporter, demonstrating that SiaA/D connects c-di-GMP and RsmA/rsmY/Z signaling to reciprocally regulate cell aggregation in response to environmental conditions.